Nutritional Value and Sensory Properties of Brown Rice Flour Cookies with Green Spinach (Amaranthus Tricolor L.) Incorporation as Gluten-Free Food Alternative - Mahmudah, Nur Aini; Nur Mauizza, Raissa; Nabawiyah, Hafidhotun; Yuni Damayanti, Amilia (Faculty of Agricultural Technology, Universitas Semarang, 2023)
Cookies is one of the wheat-based snack product with increasing rate of consumption by years. Wheat flour used in Indonesia is fully imported. Local crop product such as brown rice flour with respective nutritional aspect can be utilized for wheat substitution. Addition of spinach as green leafy vegetable with numerous nutrients gives more functional value to the product. This research aimed to investigate the acceptability (sensory properties) and nutritional content of brown rice flour cookies with the addition of green spinach. Four formulations made with ratio of brown rice and green spinach which were 100:0, 90:10, 85:15, 80:20. There were significant differences in protein, fat, and carbohydrate content among the four cookies samples There were significant differences in color appearance and taste between all samples. The best treatment is at the ratio of brown rice flour 90: green spinach 10, containing moisture content of 3.83%; ash content 1.48%; protein content 10.97%; fat content 31%; carbohydrates 52.7%; and crude fiber content of 17.3%.